Analisis Kelayakan Investasi Pengembangan Perumahan Subsidi di Kabupaten Aceh Tamiang - Firdasari Firdasari; Meilandy Purwandito; Syahfitriani Syahfitriani (Jurnal Serambi Engineering, 2022)
The construction of subsidized housing projects continues to increase every year. This development must be in line with the benefits received by developers of subsidized housing, especially regarding investment costs, which need to be analyzed for suitability based on the benefits obtained. The developers need to make a decision in allocating the amount of funds they currently have, with the aim of gaining profits and increasing that value in the future. The technical aspect determines that the developers have carried out development in accordance with the standards set by the government. Analysis of housing investment needs to be carried out, including from the technical and financial aspects, to find out how much benefit has been obtained from the housing business that has been going on so far. The review of the technical aspects includes the height of the subsidized house building, the Basic Building Coefficient (BBC), the Building Floor Coefficient (BFC) and the accessibility of the location. Furthermore, the analysis of financial aspects using the Net Present Value (NPV) and Benefit Cost of Ratio (BCR) methods. From the results obtained, the construction of Mutiara Residence II Housing in Aceh Tamiang Regency has met the requirements from the technical aspect with a building height of 15 m, BBC and BFC 30% as well as accessibility close to the city center, offices, houses of worship and health centers, with mileage less than 10 minutes. The feasibility of the financial aspect is calculated using the NPV and BCR methods with NPV 0 and BCR 1, so the cash flow for proper investment and meets to be implemented for the development of subsidized housing development. The return on investment obtained ranges from 8% to 10%. From the results of the projection for the development of subsidized housing development using sensitivity analysis, an addition of 20% was carried out on certain elements, it was found that from a financial aspect it was still adequate and feasible to add 20% with the selling price in accordance with government regulations which increased every year.